2003
DOI: 10.1093/jn/133.7.2440s
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol: A Candidate Nutritional Substance for Prostate Cancer Prevention

Abstract: The dietary stilbene resveratrol is a major constituent of a variety of edible plant products, including grapes and peanuts. Resveratrol has been identified as an excellent candidate cancer chemopreventive, based on its safety and efficacy in animal models of carcinogenesis. Resveratrol is a prototype of a plethora of bioactive polyphenols in the food supply that has just begun to be mined for cancer preventive agents. For example, polyphenolic grapeseed fractions were shown recently to potently antagonize che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 25 publications
2
51
0
5
Order By: Relevance
“…In the first report of resveratrol as a possible cancer chemopreventive agent, Jang et al (11) reported that resveratrol exerts antitumor properties at all three stages of skin carcinogenesis, including initiation, promotion, and progression. Since then, other studies have confirmed this work, and resveratrol has been shown to have chemopreventive properties in many cancer types, including mammary, prostate, colon, and lung carcinogenesis (12)(13)(14)(15). Its role in prevention and therapy of cancers of several target organs has been extensively reviewed (1,(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 67%
“…In the first report of resveratrol as a possible cancer chemopreventive agent, Jang et al (11) reported that resveratrol exerts antitumor properties at all three stages of skin carcinogenesis, including initiation, promotion, and progression. Since then, other studies have confirmed this work, and resveratrol has been shown to have chemopreventive properties in many cancer types, including mammary, prostate, colon, and lung carcinogenesis (12)(13)(14)(15). Its role in prevention and therapy of cancers of several target organs has been extensively reviewed (1,(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 67%
“…Consequently, resveratrol has been extensively studied, and numerous beneficial effects have been observed, including antithrombotic, cardioprotective, anti-inflammatory, antioxidative, and vasorelaxant effects (Bhat et al, 2001;Delmas et al, 2005;KasdallahGrissa et al, 2007;Stef et al, 2006;). In addition, resveratrol exhibits antitumor properties in several cancer types, including prostate, mammary, colon, and lung cancers (Bhat and Pezzuto, 2002;Revel et al, 2003;Schneider et al, 2000;Stewart et al, 2003). The anticancer effects of resveratrol are associated with its ability to suppress proliferation and induce apoptosis through a variety of different pathways in tumor cell lines (Aggarwal et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Oak-aged red wine [175] Overwelming evidence can be found in the literature on the proapoptotic properties of dietary polyphenols against numerous types of human cancer cell lines, from colon and prostate cancers, to breast adenocarcinoma and leukaemia [176,177]. Among many others apoptosis was reported to be induced by anthocyanidins [166] and epicathechin in hepatoma cell lines; by epigallocatechin-3-gallate (EGCG) [178] and pterocarnin [179] in breast adenocarcinoma MCF-7 cells; by quercetin in oral squamous carcinoma [137], leukaemia [180,181], breast [182,183], lung [184], prostate [185,186] and colon cancer cell lines [187]; by gallotannin in human colon cancer cell lines [188]; by resveratrol in prostate cancer [189]; by genistein in breast [190,191], prostate [192,193], gastrointestinal [194], lung [195], and head and neck cancer cell lines [196,197]; by persimmon extract (Diospyros kaki) and related polyphenols in lymphoid leukaemia cells [198] or by olive oil polyphenol-rich extract in AGS stomach cancer cells [199].…”
Section: Chemopreventive Dietary Componentsmentioning
confidence: 99%